2019
DOI: 10.1002/anie.201910478
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healable Solid Polymeric Electrolytes for Stable and Flexible Lithium Metal Batteries

Abstract: The key issue holding back the application of solid polymeric electrolytes in high‐energy density lithium metal batteries is the contradictory requirements of high ion conductivity and mechanical stability. In this work, self‐healable solid polymeric electrolytes (SHSPEs) with rigid‐flexible backbones and high ion conductivity are synthesized by a facile condensation polymerization approach. The all‐solid Li metal full batteries based on the SHSPEs possess freely bending flexibility and stable cycling performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(99 citation statements)
references
References 39 publications
0
99
0
Order By: Relevance
“…[1,2,[20][21][22][23] Nevertheless, the large-scale application of SPEs in LMBs is still inevitably hindered because of the sluggish transport of Li ions and poor affinity of the Li/electrolyte interface. [24][25][26][27][28] Considering the ultrahigh reducibility of Li, serious parasitic reactions (e.g., Li reacts with poly(ethylene oxide) (PEO) to form Li 2 O, C 2 H 4 , and H 2 ) inevitably occur at the Li/PEO interface to harm the performances of batteries. [29][30][31][32] Moreover, the Li/ PEO interface may be continuously thickened during the battery operation originated from the repeated reactions between fresh SPE and Li (Figure 1a), resulting in large electrochemical impedance and uneven surface morphology.…”
Section: Doi: 101002/adma202000223mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2,[20][21][22][23] Nevertheless, the large-scale application of SPEs in LMBs is still inevitably hindered because of the sluggish transport of Li ions and poor affinity of the Li/electrolyte interface. [24][25][26][27][28] Considering the ultrahigh reducibility of Li, serious parasitic reactions (e.g., Li reacts with poly(ethylene oxide) (PEO) to form Li 2 O, C 2 H 4 , and H 2 ) inevitably occur at the Li/PEO interface to harm the performances of batteries. [29][30][31][32] Moreover, the Li/ PEO interface may be continuously thickened during the battery operation originated from the repeated reactions between fresh SPE and Li (Figure 1a), resulting in large electrochemical impedance and uneven surface morphology.…”
Section: Doi: 101002/adma202000223mentioning
confidence: 99%
“…[29][30][31][32] Moreover, the Li/ PEO interface may be continuously thickened during the battery operation originated from the repeated reactions between fresh SPE and Li (Figure 1a), resulting in large electrochemical impedance and uneven surface morphology. [27,33,34] These evolutions at the Li/PEO interface will lead to evident capacity fading with the inferior cyclability. [24,33,35] Tremendous strategies have been proposed to address the intractable issues in the Li/PEO interface, including constructing 3D matrix for Li metal, designing artificial SEI layers, and fabricating the mechanically strong SPEs.…”
Section: Doi: 101002/adma202000223mentioning
confidence: 99%
“…They also show good thermal stability, high mechanical rigidity, and nonflammability. [110][111][112] Common SSEs include polymer electrolytes, [113][114][115] polymer-inorganic composite electrolytes, [116][117][118] and inorganic electrolytes. [119][120][121] Amongst these, inorganic electrolytes have received great attention due to their high ionic conductivity and extremely high Young's modulus, which can enhance the safety of Li-metal batteries.…”
Section: Composite Anodes In Solid-state Batteriesmentioning
confidence: 99%
“…The addition of succinonitrile plasticizer allows the electrolyte to reach an excellent conductivity that even exceeds 10 −4 S•cm −1 at room temperature. Recently, Wu et al reported a self-healing solid polymer electrolyte (SHSPE) that is crosslinked by the dynamic intermolecular hydrogen bond between urea and ester groups located in the PEO chains [96]. The authors indicated that the inter-chain hydrogen bond and attractive Coulombic forces among the ions in the lithium salt facilitate fast self-healing.…”
Section: Crosslinked Polymermentioning
confidence: 99%